2003
DOI: 10.1051/0004-6361:20031148
|View full text |Cite
|
Sign up to set email alerts
|

A molecular gas bridge between the Taffy galaxies

Abstract: Abstract. The Taffy Galaxies system, UGC 12914/5, contains huge amounts of molecular gas in the bridge region between the receding spirals after a direct collision. 2−9 × 10 9 M of molecular gas is present between the galaxies, more than the CO emission from the entire Milky Way! Such dense gas can only be torn off by collisions between dense clouds, in this case with relative velocities of about 800 km s −1 , such that the remnant cloud acquires an intermediate velocity and is left in the bridge after separat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 54 publications
(115 citation statements)
references
References 11 publications
7
106
2
Order By: Relevance
“…We thus conclude that the bridge region delimited by Braine et al (2003, Fig. A.1) is somewhat too small.…”
Section: Isolating the Bridge Regionmentioning
confidence: 76%
See 2 more Smart Citations
“…We thus conclude that the bridge region delimited by Braine et al (2003, Fig. A.1) is somewhat too small.…”
Section: Isolating the Bridge Regionmentioning
confidence: 76%
“…In the Taffy system, this conversion factor varies significantly between the disk and bridge regions (Braine et al 2003;Zhu et al 2007). Because of the uncertainty of the local conversion factor, we apply a constant Galactic CO-H 2 conversion factor N(H 2 )/I CO = 10 20 cm −2 (K km s −1 ) −1 to the whole Taffy system (Zhu et al 2007).…”
Section: Gas Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…low impact parameter), in which the ISM of the progenitors collides. The best example of this is UGC 12914/5 (the Taffy Galaxies; Braine et al 2003), in which about 25% of the CO emission originates between the nuclei. In this system, the progenitors collided at about 600 km s −1 .…”
Section: Merger Geometry and Stage And Cold Gas Concentrationmentioning
confidence: 99%
“…In this system, the progenitors collided at about 600 km s −1 . Braine et al (2003) argued that while this would have ionised the gas, the cooling time is short enough that H 2 could reform while the discs are still passing through each other. From the ratio of 12 CO to 13 CO these authors found that the optical depth of CO in the bridge was far less than on the nuclei.…”
Section: Merger Geometry and Stage And Cold Gas Concentrationmentioning
confidence: 99%